Prognostic value of kallikrein-related peptidase 12 (KLK12) mRNA expression in triple-negative breast cancer patients - Gong, Weiwei; Liu, Yueyang; Preis, Sarah; Geng, Xiaocong; Petit-Courty, Agnes; Kiechle, Marion; Muckenhuber, Alexander; Dreyer, Tobias; Dorn, Julia; Courty, Yves; Magdolen, Viktor (Molecular medicine (Cambridge, Mass.), 2020)
Background The serine protease KLK12 belongs to the human fifteen-member family of kallikrein-related peptidases. Differential expression accompanied by either increased or decreased enzymatic activity has been linked to several diseases including cancer. Triple-negative breast cancer (TNBC) represents a very aggressive subgroup of breast cancer with high tumor recurrence rates and poor patient prognosis. Here, we quantified the KLK12 mRNA expression levels in tumor tissue of TNBC patients and analyzed their prognostic value. Methods In the present study, KLK12 mRNA expression in tumor tissue of TNBC patients ( n = 116) was determined by quantitative real-time PCR assay. The association of KLK12 mRNA levels with clinical parameters, and patients’ outcome was analyzed using Chi-square tests, Cox regression models and Kaplan-Meier survival analysis. Results Positive, but low KLK12 mRNA levels were detected in about half of the cases (54 out of 116; 47%), the other samples were negative for KLK12 mRNA expression. No significant association was observed between KLK12 mRNA levels and clinicopathological variables (age, lymph node status, tumor size, and histological grade). In univariate Cox analyses, positive KLK12 mRNA expression was significantly associated with shortened disease-free survival (DFS; hazard ratio [HR] = 2.12, 95% CI = 1.19–3.78, p = 0.010) as well as overall survival (OS; HR = 1.91, 95% CI = 1.04–3.50, p = 0.037). In multivariable Cox analysis, including all clinical parameters plus KLK12 mRNA, the latter - together with age - remained an independent unfavorable predictive marker for DFS (HR = 2.33, 95% CI = 1.28–4.24, p = 0.006) and showed a trend towards significance in case of OS (HR = 1.80, 95% CI = 0.96–3.38, p = 0.066). Conclusions Positive KLK12 expression is remarkably associated with shortened DFS and OS, suggesting that KLK12 plays a tumor-supporting role in TNBC.